Ancient Geographical Barriers Drive Differentiation among Sonneratia caseolaris Populations and Recent Divergence from S. lanceolata - Yang, Yuchen; Duke, Norman C.; Peng, Fangfang; Li, Jianfang; Yang, Shuhuan; Zhong, Cairong; Zhou, Renchao; Shi, Suhua (Frontiers in Plant Science, 2016)
Glacial vicariance is thought to influence population dynamics and speciation of many marine organisms. Mangroves, a plant group inhabiting intertidal zones, were also profoundly influenced by Pleistocene glaciations. In this study, we investigated phylogeographic patterns of a widespread mangrove species Sonneratia caseolaris and a narrowly distributed, closely related species S. lanceolata to infer their divergence histories and related it to historical geological events. We sequenced two chloroplast fragments and five nuclear genes for one population of S. lanceolata and 12 populations of S. caseolaris across the Indo-West Pacific (IWP) region to evaluate genetic differentiation and divergence time among them. Phylogenetic analysis based on sequences of nuclear ribosomal internal transcribed spacer and a nuclear gene rpl9 for all Sonneratia species indicate that S. lanceolata individuals are nested within S. caseolaris. We found strong genetic structure among geographic regions (South China Sea, the Indian Ocean, and eastern Australia) inhabited by S. caseolaris. We estimated that divergence between the Indo-Malesia and Australasia populations occurred 4.035 million years ago (MYA), prior to the onset of Pleistocene. BARRIERS analysis suggested that complex geographic features in the IWP region had largely shaped the phylogeographic patterns of S. caseolaris. Furthermore, haplotype analyses provided convincing evidence for secondary contact of the South China Sea and the Indian Ocean lineages at the Indo-Pacific boundary. Demographic history inference under isolation and migration (IM) model detected substantial gene flow from the Sri Lanka populations to the populations in the Java Island. Moreover, multi-locus sequence analysis indicated that S. lanceolata was most closely related to the Indian Ocean populations of S. caseolaris and the divergence time between them was 2.057 MYA, coinciding with the onset of the Pleistocene glaciation. Our results suggest that geographic isolation driven by the Pleistocene ice age resulted in the recent origin of S. lanceolata.